2011
DOI: 10.1038/nature10116
|View full text |Cite
|
Sign up to set email alerts
|

Induction of functional hepatocyte-like cells from mouse fibroblasts by defined factors

Abstract: The generation of functional hepatocytes independent of donor liver organs is of great therapeutic interest with regard to regenerative medicine and possible cures for liver disease. Induced hepatic differentiation has been achieved previously using embryonic stem cells or induced pluripotent stem cells. Particularly, hepatocytes generated from a patient's own induced pluripotent stem cells could theoretically avoid immunological rejection. However, the induction of hepatocytes from induced pluripotent stem ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
705
2
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 776 publications
(733 citation statements)
references
References 29 publications
(40 reference statements)
19
705
2
7
Order By: Relevance
“…Another example of transdifferentiation across germ layers is when hepatocyte-like cells are induced from fibroblasts (iHep) by exogenous expression of either forkhead box protein A1 (FoxA1), FoxA2, or FoxA3 with HNF4a (Sekiya and Suzuki 2011) or exogenous expression of FoxA3, GATA4, and HNF1a in combination with the inactivation of the tumor suppressor gene p19 Arf (Huang et al 2011). These factors were discovered from pools of many transcription factors involved in liver development; the common component was FoxA.…”
Section: Espinosa and Emerson 2001mentioning
confidence: 99%
See 1 more Smart Citation
“…Another example of transdifferentiation across germ layers is when hepatocyte-like cells are induced from fibroblasts (iHep) by exogenous expression of either forkhead box protein A1 (FoxA1), FoxA2, or FoxA3 with HNF4a (Sekiya and Suzuki 2011) or exogenous expression of FoxA3, GATA4, and HNF1a in combination with the inactivation of the tumor suppressor gene p19 Arf (Huang et al 2011). These factors were discovered from pools of many transcription factors involved in liver development; the common component was FoxA.…”
Section: Espinosa and Emerson 2001mentioning
confidence: 99%
“…These factors were discovered from pools of many transcription factors involved in liver development; the common component was FoxA. However, compared with primary hepatocytes, iHeps show significant differences in gene expression and are unable to fully rescue liver function in a transplantation model (Huang et al 2011;Sekiya and Suzuki 2011). CellNet analysis, which is a bioinformatics tool to assess the fidelity of cell conversion, surprisingly revealed that iHeps induced by FoxA and HNF4a represent gut endoderm progenitors more than mature hepatocytes .…”
Section: Espinosa and Emerson 2001mentioning
confidence: 99%
“…Japanese research teams 8 were screening the effects of twelve transcription factors for conversion of mouse embryonic and adult fibroblasts into hepatocyte like cells, finally they found three specific combinations of two transcription factors, comprising Hnf4a plus Foxa1, Foxa2 or Foxa3 is sufficient for generation of hepatocyte like cells. In the same time, Chinese research teams 9 reported in independently that new cocktails of transcription factors of Gata4, HNF1alpha, Foxa3, and RNAi-mediated inactivation of p19Arf for direct induction of functional hepatocyte like from mouse tail-tip fibroblasts. Yu et al, 10 brilliantly decided to explore two liver organogenesis transcription factors Hnf1b and Foxa3, to reprogram mouse embryonic fibroblasts into induced hepatic stem cells and successfully converted to induced hepatic stem cells from mouse embryonic fibroblasts.…”
Section: Commentsmentioning
confidence: 99%
“…Recently, researchers used such liver specific transcription factors for generation of hepatocyte cells from skin fibroblast cells in vitro. [8][9][10][11][12] The ultimate aim of generation of hepatocytes from skin cells to treat liver diseases. If we know the transcription factors and small molecules which have potential to convert hepatocyte from fibroblast, why not to explore transcription factors and small molecules in vivo directly to repair or regenerating the tissue or organs.…”
Section: Commentsmentioning
confidence: 99%
“…In recent years, China has published many important discoveries related to the research of translational medicine. Some of the major themes touched by these publications include: research into mechanisms of diseases with the aim of identifying new therapeutic targets or improved therapeutic strategies [5-18], "omics" approaches to human diseases [19][20][21][22][23][24][25][26], testing of new therapeutic methods in animal models [27-31], research into the mechanisms of host immune defense against infections [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48], and regenerative medicine-related research [49][50][51][52][53][54][55][56][57]. However, our understanding of human diseases remains limited, the move from bedside to bench must continue to be pursued.…”
mentioning
confidence: 99%